On the oscillation of delay differential equations with real coefficients - H. A. Agwo (International Journal of Mathematics and Mathematical Sciences)
A set of necessary conditions and another set of sufficient conditions for the oscillation of all the solutions of x˙(t)+∑i=1npix(t−τi)=0,         where   pi∈ℝ,  τi∈ℝ+,    i=1,2,…,n                                   (*) are proved.